Quaternary sedimentology and tephrostratigraphy of the lower Pohangina Valley, New Zealand. Issue 2 (3rd April 2019) - Rees, Callum; Palmer, Alan; Palmer, Julie
ABSTRACT: Shallow-marine to fluvio-estuarine deposits in Pohangina Valley represent an underexplored portion of the Whanganui Basin, a globally significant archive of Quaternary climate change. To address this, we document environments of deposition through facies analysis, tephrostratigraphy and biostratigraphy. The marine shelf environment is characterised by fossiliferous mudstone containing marine Mollusca. Estuarine facies consist of pumiceous sandstone, tephra, lignite and carbonaceous mudstone. Volcaniclastic and tephra-fall deposits record seven eruptions from the Taupo Volcanic Zone between c. 1.6 and 0.9 Ma. We identify and define Awahou Tephra (new) (c. 1.03 Ma), through mapping and geochemical analysis of constituent glass shards. Progressive retreat of the sea (c. 1.6 Ma) is indicated by a change from shallow-marine to fluvio-estuarine sedimentation. An east–west drainage system developed (c. 1 Ma), including ponding near Woodville from which an early ancestor of the Manawatu River exited, establishing an antecedent path to the Tasman Sea across the uplifting paleo-axial range.